2014
DOI: 10.1590/s0102-86502014000300001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Annona muricata (soursop) on biodistribution of radiopharmaceuticals in rats

Abstract: The A. muricata hydroalcoholic extract negatively influenced the uptake of 99mTc-DMSA in bladder, kidney and blood of rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…However, such danger can be averted if the extract is used over a short period of time, as the effect is observed to be time and concentration dependent. The research find is in line with the finding of (Arthur et al, 2011;Holanda et al, 2014) in which both expresses insignificant effect on the liver function parameters and the later even reported histo-protective potential of the plant extract. However the variations noted with the current work are, both authors worked on aqueous extract.…”
Section: Table 5 Effect Of Annona Muricata (L) Methanol Extract On Sosupporting
confidence: 90%
“…However, such danger can be averted if the extract is used over a short period of time, as the effect is observed to be time and concentration dependent. The research find is in line with the finding of (Arthur et al, 2011;Holanda et al, 2014) in which both expresses insignificant effect on the liver function parameters and the later even reported histo-protective potential of the plant extract. However the variations noted with the current work are, both authors worked on aqueous extract.…”
Section: Table 5 Effect Of Annona Muricata (L) Methanol Extract On Sosupporting
confidence: 90%
“…In this study, fructose was also not able to change this biodistribution. This result is consistent with the results obtained by Holanda et al (2014), who investigated the biodistribution of 99m Tcsodium phytate in the liver, spleen and blood of rats fed food rich in fructose (soursop) and observed no change in their uptake.…”
Section: Discussionsupporting
confidence: 93%
“…The authors attribute this result, possibly inhibition of carnitine palmitoyltransferase I enzyme (CPTI) involved in the beta oxidation, which leads to an accumulation of fatty acids in the liver and induces liver damage (Song et al, 2012). In a study by Holanda et al (2014), it was observed that the use of Annona muricata extract (soursop) (25 mg/kg/day), which is a rich source of fructose, did not significantly alter the levels of AST and ALT. The changes in hepatic enzymes (AST and ALT) caused by consumption of fructose in studies by Song et al (2012) were due to different concentrations of the A. muricata extract and high dose used by the authors (50 mg/kg/day).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite their benefits, hepatotoxic effects have been reported with the use of herbal medicines in rats, probably due to the alcohol in their composition 30 . Therefore, in this study, the effects of administering mastruz extract in rats with induced OP were evaluated by means of histological and biochemical analyses.…”
mentioning
confidence: 99%